Pengaruh Kepemilikan Institusional dan Kepemilikan Manajerial terhadap Manajemen Laba dengan Leverage sebagai Variabel Moderating: Studi pada Perusahaan Manufaktur yang Tercatat di Bursa Efek Indonesia Tahun 2019 - 2023 - Eka Pratiwi,; Abdul Pattawe,; Ni Made Suwitri Parwati, (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study aims to examine and analyze the effect of institutional ownership and managerial ownership on earnings management, with leverage acting as a moderating variable. The population in this study comprises manufacturing companies listed on the Indonesia Stock Exchange in 2023, totaling 165 companies. The research sample was selected using a purposive sampling technique, resulting in a total of 165 observations from the 2019–2023 period. The analytical method used is SEM-PLS (Structural Equation Modeling - Partial Least Squares) with the assistance of WarpPLS 8.0 software. The results of this study indicate that institutional ownership has no effect on earnings management, whereas managerial ownership has a significant negative effect on earnings management. Furthermore, leverage strengthens the effect of institutional ownership, but it weakens the effect of managerial ownership on earnings management. Future research is expected to incorporate additional Good Corporate Governance (GCG) mechanism variables and extend the observation period so that the dynamics of post-pandemic macroeconomic changes can be documented more accurately.